The Relationship Of Motivation With Nurses' Performance - Maemunah, Neni; Susmini, Susmini; Bili, Rustiana Nona (Jurnal Surya, 2024)
Introduction: The high commitment of nurses in providing optimal health services to patients is an illustration of the seriousness of nurses to maintain the quality of services provided by hospitals. The aim of the research is todetermine the relationship between motivation and performance commitment of nurses.Methods: The research design used cross sectional. The research population was 65 nurses with a sample size of 56 nurses. Samples were taken using simple random sampling technique. The independent variable is motivation, the dependent variable is nurse performance commitment. The instrument used was a questionnaire. Data analysis used Fisher's exact test.Results: The results of this research show that the majority of respondents have motivation in the good category, some respondents have performance in the good category and there is a relationship between motivation and the performance commitment of nurses with a value of p value = ( 0.018) < (0.05). Conclusion: There is a relationship between motivation and performance commitment of nurses. Factors that affect motivation and performance, namely workload and length of work can be used as topics for future researchKeywords: Motivation, Performance Commitment, Hospitals, Nurses.